A comprehensive interventional program based on the needs and concerns related to female genital cosmetic surgeries: protocol for a multistage mixed methods study - Zahra Ghorbani; Zahra Behboodi Moghadam; Mojgan Mirghafourvand; Faezeh Vahidnia; Elham Ebrahimi (BMC, 2023)
Abstract Background Dissatisfaction with one's body and the subsequent rise in the cosmetic surgery trend pose significant public health concerns today. One unusual cosmetic surgical procedure involves enhancing the genital area. Numerous healthy women and girls have recently sought Genital Cosmetic Surgery (GCS) for beauty or improved sexual performance. There is a concern that this phenomenon may be linked to developing a new standard for vulvovaginal appearance. This stringent standard could potentially adversely affect women's mental health in the future, growing feelings of insecurity and possibly leading teenagers to consider plastic surgery. Implementing empowering and awareness-raising programs for women and girls is crucial, especially in light of the constantly evolving gender norms and the medicalization of sexuality and beauty as social constructs. It is essential that such training is integrated into comprehensive sexual education programs for adolescents. These efforts align perfectly with the SDG, recognizing that education in sexual and reproductive health, ensuring access to health, and empowering women are fundamental rights for women and girls. To accomplish these objectives, we will conduct this study to elucidate the needs and concerns related to the increasing trend of GCS. By doing so, we can concentrate on the factors motivating women to undergo GCS. This approach will enable us to develop effective interventions to empower women and girls considering GCS, thus enhancing their sexual and reproductive health. Methods and objectives The objectives of this multistage exploratory sequential mixed-method study will be structured into three phases: First phase: qualitative study. 1. In-depth interviews will be conducted to elucidate the needs and concerns associated with GCS with women with a history of GCS, spouses of willing participants, and women actively seeking these procedures. 2. A literature review in parallel with the qualitative phase will be conducted to gain insights into the needs and concerns of women worldwide considering GCS. Second phase: program design. 1. To formulate an intervention grounded in the primary priorities identified during the qualitative stage and informed by the literature review. 2. To prioritize the needs and concerns of women seeking GCS and to validate and endorse the intervention through input from an expert panel. Third phase: quantitative study. To assess and determine the effectiveness of the intervention designed to address the needs and concerns of women applying for GCS procedures. Discussion This study marks the first attempt to design and assess an intervention addressing the needs and concerns of cosmetic surgeries performed on the female genital and reproductive system. The hope is that this study's compilation and implementation will yield substantial evidence and documentation regarding the impact of educational interventions on women's and girls' sexual and reproductive empowerment. Given the rising prevalence of GCS among unmarried teenagers, this approach is of utmost significance. It underscores the necessity for gynecological and midwifery service providers to have comprehensive guidance on GCS. Such guidance can be an essential resource for healthcare providers in this field.